A Semiotic Model to Investigate Sensory Metaphors by Comparing Architectural Photorealistic Rendered Images and Actual Constructed Buildings - Rasiha Kayalar; Erçim Uluğ (SAGE Open)
Photorealistic rendered images are the visuals of an architectural project which is not constructed but its design process is completed. They are presented to society and clients to represent what the building will look like. These images are typically presented to the public as a marketing strategy. In this regard, the photorealistic rendered images are pre-imaging of the actual constructed building. However, it is important to understand if these two mediums (dimensions) are semantically connoted same or different. Therefore, this research aims to analyse and understand these possible similarities and differences. It aims to reveal the metaphoric differences in terms of “architectural experiences” by a developed model in semiotics which is based on analysis of user experience’s systematic codification. In conclusion, this paper develops a research method that aims to demonstrate the connotation differences and it discusses how the mental attitude can be affected. In this regard, it explains how the representations of photorealistic renders create positive but misleading user experiences.